Thioredoxin Reductase Inhibitors as Potential Antitumors: Mercury Compounds Efficacy in Glioma Cells - Pires, Vanessa; Bramatti, Isabella; Aschner, Michael; Branco, Vasco; Carvalho, Cristina (Frontiers in Molecular Biosciences, 2022)
Glioblastoma multiforme (GBM) is the most aggressive and common form of glioma. GBM, as many other tumors, expresses high levels of redox proteins, such as thioredoxin (Trx) and thioredoxin reductase (TrxR) allowing tumor cells to cope with high levels of reactive oxygen species (ROS) and resist to chemotherapy and radio therapy. Thus, tackling the activity of these enzymes is a strategy to reduce cell viability and proliferation. and most importantly, achieve tumor cell death. Mercury (Hg) compounds are among the most effective inhibitors of TrxR and Trx due to their high affinity for binding thiols and selenols. Moreover, organomercurials such as thimerosal, have an history of clinical use in humans. Thimerosal effectively crosses the blood brain barrier (BBB), thus reaching effective concentrations for the treatment of GBM. Therefore, this study evaluated the effects of thimerosal (TmHg) and its metabolite ethylmercury (EtHg) over the mouse glioma cell line (GL261), namely, the inhibition of the thioredoxin system and the occurrence of oxidative cellular stress. The results showed that both TmHg and EtHg increased oxidative events and triggered cell death primarily by apoptosis, leading to a significant reduction in GL261 cell viability. Moreover, the cytotoxicity of TmHg and ETHg in GL261 was significantly higher when compared to temozolomide (TMZ). These results indicate that EtHg and TmHg have potential to be used in GBM therapy, since they strongly reduce the redox capability of tumor cells at exceedingly low exposure levels.